ANALISIS MUTU RBDPO (REFINED BLEACHED AND DEODORIZED PALM OIL) PADA PROSES REFINERY DI PT X - Desniorita Desniorita; Sutri Apriani (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
PT X Padang is one of the factories that processes CPO (Crude Palm Oil) into Olein commonly called cooking oil. The process of making olein is done through several stages of the process such as degumming, bleaching, filtration, deodorization and fractionation. The purpose of the analysis carried out is to analyze how much the quality deviation of RBDPO is Free Fatty Acid (FFA), color and Iodin Value by using the mean chart control chart (X) and control chart range (R), identifying the causes of quality problems (deviations) RBDPO with a causal diagram (fishbone), provides improvement proposals to improve the quality of RBDPO that occurred at PT. X Padang. The results of processing are the number of samples outside the control limit for FFA levels of 6 samples with a percentage of 37.5%, color that is 10 samples with a percentage of 62.5%, and Iodin Value which is 0 samples. The most dominant causes when viewed with fishbone diagrams are human, machine and material factors. From the results of the analysis it can be concluded that RBDPO products at PT X still have data that is beyond the control limits. The main causes are influenced by human, machine and material factors, so prevention must be done by examining the problems that occur and taking corrective actions.